Effect of training on the temperature memory effect in Ti49.5Ni34.5Cu11.5Pd4.5 shape memory alloy with narrow hysteresis. (June 2016) - Meng, X.L.; Li, Hang; Cai, W.
Abstract: The temperature memory effect (TME) has been investigated in Ti49.5 Ni34.5 Cu11.5 Pd4.5 alloy with a narrow hysteresis. The TME can be enhanced through multiple partial thermal cycling (TME training). The TME obtained by training is repeatable and hard to wipe out, which can be detected even after 1000 following complete thermal cycles. A difference in the dislocation density between different martensite regions is introduced during training, which results in the TME. It increases with increasing training cycles, and graduates away slowly because of the rare introduced dislocations during the following complete thermal cycles, leading to the repeatable TME. Graphical abstract: